The Missing Link between Corporate Social Responsibility and Financial Performance: Stakeholder Salience and Identification - Peloza, John; Papania, Lisa (Corporate reputation review, 2008)
In this paper, we present a framework for examining the relationship between corporate social responsibility (CSR) and firm financial performance. Ambiguity in empirical studies examining this relationship can be expected given both the ability and motivation of managers to focus their social responsibility initiatives on stakeholders with power, urgency and legitimacy. By considering the ability of stakeholders to reward or punish the firm based on their evaluations of the firm's activities, our model reconciles previously disparate findings in the relationship between CSR and corporate financial performance.